The Ecclesiology of the Latitude-men 1660–1689: Stillingfleet, Tillotson and 'Hobbism' - Marshall, John (The journal of ecclesiastical history, 1985)
When the redoubtable Presbyterian Richard Baxter came to write his engagingly biased autobiography he distinguished three broad categories of conformists to the Restoration Church Settlement of 1662. There were those who had been forced to conform out of need, or had casuistically placed their own meaning on the words of the Subscription; next there were the Latitudinarians, who were ‘mostly Cambridge-men’ and of ‘Universal Principles and free’; and then there were those of the ‘high and swaying Party’ who were ‘desirous to extirpate or destroy the Nonconformists’.